Digital Encyclopedia of Applied Physics 2019
DOI: 10.1002/3527600434.eap857
|View full text |Cite
|
Sign up to set email alerts
|

GaN‐On‐Si Epitaxy

Abstract: The wide‐bandgap semiconductor GaN is the enabler for light emitters in the visible to UV spectrum and for energy‐efficient high‐frequency and high‐power electronics. Due to the lack of GaN homosubstrates, GaN is mostly grown on heterosubstrates as sapphire, Si, or SiC by molecular beam epitaxy or in industry by metalorganic chemical vapor‐phase epitaxy. With Si being a low‐cost substrate available in large diameters, low‐cost mass production of GaN devices, especially of GaN electronics, is favorable on silic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 125 publications
0
3
0
Order By: Relevance
“…Dual-finger gate and depletion mode HEMTs were structured with gate width and length of W G = 50 µm and L G = 1.5 µm, respectively, and with source-gate and sourcedrain spacing of S G = 1.5 µm and S D = 4.5 µm, respectively. Each HEMT has a dimension of 650 × 450 µm 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dual-finger gate and depletion mode HEMTs were structured with gate width and length of W G = 50 µm and L G = 1.5 µm, respectively, and with source-gate and sourcedrain spacing of S G = 1.5 µm and S D = 4.5 µm, respectively. Each HEMT has a dimension of 650 × 450 µm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…These HEMTs also include an ultra-thin AlN spacer layer for further improvement of the conductivity of the channel region. High quality epitaxial growth of these structures can be realized on large size Si(111) substrates by metalorganic vapor-phase epitaxy (MOVPE), which is attractive as an economically prospective technology for GaN-based HEMT transistors [2]. Studies have shown that for GaN on Si HEMTs vertical leakage current associated defects in the buffer layer limit breakdown voltage [3].…”
Section: Introductionmentioning
confidence: 99%
“…This introduces high edge-and screw-dislocation densities, as well as hexagonal macro defects and even cracks [2,60]. While GaN maintains its hexagonal lattice and epitaxial relationship with Si (111) in a straightforward manner, the GaN hexagonal lattice is spontaneously rotated by 30 • when grown onto the trigonal lattice of sapphire (see figure 3) [61]. Interestingly, this allows the GaN lattice to align with the corresponding sapphire lattices and produces a ∼16% coincidental lattice mismatch instead of the ∼33% expected if we were to calculate the lattice mismatch value using the free-standing lattice constants of GaN and sapphire [62].…”
Section: Mismatch Between Epitaxy and Substratesmentioning
confidence: 99%